2005
DOI: 10.1016/j.colsurfa.2004.10.123
|View full text |Cite
|
Sign up to set email alerts
|

Trapped non-equilibrium states in aqueous solutions of oppositely charged polyelectrolytes and surfactants: effects of mixing protocol and salt concentration

Abstract: The very slow equilibration time in oppositely charged systems makes it necessary to control not only the concentration of the species but also the details of the mixing process. This has been demonstrated for processes occurring at interfaces where order of addition effects can be of great importance. In this investigation we set out to study the bulk properties of aqueous mixtures of a highly charged cationic polyelectrolyte mixed with an anionic surfactant with the aim to learn if long-lived non-equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
127
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 32 publications
(38 reference statements)
11
127
0
1
Order By: Relevance
“…In cases where the amphiphylic species are negatively charged, e.g. with carboxylate or sulfonate groups, relatively strong interactions with cationic polyelectrolytes have been documented (Dubin and Davis 1985;Leung and Goddard 1985;Naderi et al 2005). Without calling into question the foregoing evidence of cationic demand of various extractive materials, it also has been reported that non-charged, unsaponifiable compounds may make up the majority of extractives from some species, including eucalyptus (Prinsen et al 2012).…”
Section: Figmentioning
confidence: 99%
See 4 more Smart Citations
“…In cases where the amphiphylic species are negatively charged, e.g. with carboxylate or sulfonate groups, relatively strong interactions with cationic polyelectrolytes have been documented (Dubin and Davis 1985;Leung and Goddard 1985;Naderi et al 2005). Without calling into question the foregoing evidence of cationic demand of various extractive materials, it also has been reported that non-charged, unsaponifiable compounds may make up the majority of extractives from some species, including eucalyptus (Prinsen et al 2012).…”
Section: Figmentioning
confidence: 99%
“…As was noted in Table 6, some researchers have reported that the presence of surfactants can interfere with the endpoints of polyelectrolyte titrations (Dubin and Davis 1985;Leung and Goddard 1985;Naderi et al 2005). Figure 15 represents a situation in which an anionic surfactant molecule, e.g.…”
Section: Concern About a Possible Role Of Surfactantsmentioning
confidence: 99%
See 3 more Smart Citations